Chemotherapy-induced cavitating Wilms' tumor pulmonary metastasis: Active disease or scarring? A case report and literature review - Zarfati, Angelo; Martucci, Cristina; Crocoli, Alessandro; Serra, Annalisa; Persano, Giorgio; Inserra, Alessandro (Frontiers in Pediatrics, 2023)
Wilms tumor is the second most frequent abdominal tumor in children and the lung is the most common site for its metastases. The typical metastases are multiple, peripherally located, round, and variable-sized nodules. Atypical patterns are also possible and may create diagnostic challenges, especially in patients treated with chemotherapy. Among these, cavitating metastases are an anecdotal type of atypical lung secondary lesions. Here we report a case of a chemotherapy induced cavitating Wilms' tumor pulmonary metastasis discovered during the follow-up for an anaplastic nephroblastoma in a 6-year-old girl. Furthermore, we realized a review of the existing literature on this exceedingly rare radiological pattern, to establish its best management.